(3c-8)-(-5c+3)=

Simple and best practice solution for (3c-8)-(-5c+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3c-8)-(-5c+3)= equation:


Simplifying
(3c + -8) + -1(-5c + 3) = 0

Reorder the terms:
(-8 + 3c) + -1(-5c + 3) = 0

Remove parenthesis around (-8 + 3c)
-8 + 3c + -1(-5c + 3) = 0

Reorder the terms:
-8 + 3c + -1(3 + -5c) = 0
-8 + 3c + (3 * -1 + -5c * -1) = 0
-8 + 3c + (-3 + 5c) = 0

Reorder the terms:
-8 + -3 + 3c + 5c = 0

Combine like terms: -8 + -3 = -11
-11 + 3c + 5c = 0

Combine like terms: 3c + 5c = 8c
-11 + 8c = 0

Solving
-11 + 8c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 8c = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 8c = 0 + 11
8c = 0 + 11

Combine like terms: 0 + 11 = 11
8c = 11

Divide each side by '8'.
c = 1.375

Simplifying
c = 1.375

See similar equations:

| f^2=-44 | | 2+x=-4x+12 | | 3(2x+-5)=2(3x+-1)-13 | | 28=-9(7h+4) | | -6(5-r)=12 | | 15+-2C=7 | | 2a^2-5a=0 | | 2=-4x+5x+6 | | 4x^2=-16x+4 | | 2.3x+2=12.3x+2.8x-6 | | x+15=10-x+10 | | 3A^2-4AB+B^2=0 | | 3(2x+-5)=2(3x+-1)+7 | | 5x-12=4x+20 | | -4.5x-y=3 | | 0=96x-12x^2 | | x+1.4=1.09x | | 1862=49(p+10) | | 10r^2+20=200 | | d-2d+3=3 | | 7x-4=-11-10(6-x) | | 7x^2=8x-1 | | 10+4x+4x=42 | | 14-3x=x-6 | | 5y+3y=6 | | 6a^2-28a+147=0 | | -6y-7=-37 | | 6x-3+x=5(1+x)-6 | | 6x-1=13-x | | 5x-12=4x+29 | | ln(x)=3.06 | | 3x-4-x=4 |

Equations solver categories